1994
DOI: 10.1073/pnas.91.24.11651
|View full text |Cite
|
Sign up to set email alerts
|

Elevated dopa decarboxylase activity in living brain of patients with psychosis.

Abstract: The hypofrontality theory ofthe pathogenesof schizophrenia predicts that cortical lesions caupsychosis. To test the hypothesis that the state of psychosis in temporal lobe epilepsy is associated with the same striatal supersensitivity that may cause psychosis in schizophrenia, we measured the rate of metabolism of an exogenous analog of dopa in both disorders, using positron emission tomography (PET) ofthe tracer 6-18Flfluoro-L-dopa (18F-dopa) (5,6).We have previously shown that the rate of metabolism of exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
168
1
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(188 citation statements)
references
References 30 publications
14
168
1
5
Order By: Relevance
“…In spite of these caveats, the failure to demonstrate regulation of VMAT2 by medication when post-synaptic receptors show very clear changes suggests relative insensitivity to medication status. This stands in contrast to another presynaptic dopamine marker, such as [ 18 F]DOPA (Hietala et al 1995;Reith et al 1994), which reflects activity of DOPA decarboxylase, a synthetic enzyme susceptible to negative feedback regulation via the D 2 autoreceptor (Cumming et al 1995;Young et al 1993).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In spite of these caveats, the failure to demonstrate regulation of VMAT2 by medication when post-synaptic receptors show very clear changes suggests relative insensitivity to medication status. This stands in contrast to another presynaptic dopamine marker, such as [ 18 F]DOPA (Hietala et al 1995;Reith et al 1994), which reflects activity of DOPA decarboxylase, a synthetic enzyme susceptible to negative feedback regulation via the D 2 autoreceptor (Cumming et al 1995;Young et al 1993).…”
Section: Discussionmentioning
confidence: 95%
“…Additional evidence in support of increased dopamine activity comes from demonstrations of increased metabolism of [ 18 F]fluorodopa (Dao-Castellana et al 1997;Hietala et al 1995;Reith et al 1994) and [ 11 C]L-DOPA (Lindstrom et al 1999). The prevailing interpretation of these findings is that schizophrenic patients episodically release more dopamine (Breier et al 1997;Laruelle et al 1996), possibly in connection with up-regulated enzyme activity of dopa-decarboxylase induced by low tonic activity of dopaminergic neurons (Reith et al 1994). Given the importance of this data to the pathophysiology of schizophrenia, alternative explanations need to be ruled out.…”
mentioning
confidence: 99%
“…Thus, although we cannot totally exclude the possibility that the documented changes in k D 3 are influenced by brain perfusion or tracer distribution, our study has the advantage that it actually measures these effects. Owing to numerous methodological factors, our present baseline estimates of k D 3 (Reith et al, 1994), which represents the rate constant for the decarboxylation of FDOPA, cannot be compared directly with previously reported normative values obtained by other laboratories, and cannot readily be compared with estimates of the net clearance of FDOPA (Hietala et al, 1995) or [b-11 C]DOPA (Lindström et al, 1999) to striatum K i D (ml g À1 min À1 ), which reflect the composite of perfusion, diffusion back to blood, and decarboxylation in nigrostriatal terminals. Consequently, estimates of the magnitude of K i are weighted by the unknown equilibrium volume (V e D ) of FDOPA in the brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy led to the suggestion that the antipsychotic effect of neuroleptics may arise in conjunction with the delayed depolarization block of the presynaptic neuron and reduced DA synthesis capacity, a phenomenon which occurs in experimental animals treated chronically with neuroleptics (Grace and Bunney, 1986). Several positron emission tomography (PET) studies with radiolabeled L-DOPA analogues have reported elevated activity of the enzyme DOPA decarboxylase (DDC) in the striatum of untreated patients with schizophrenia (Hietala et al, 1995;Lindström et al, 1999;Reith et al, 1994), indicating the presence of elevated capacity for DA synthesis within the terminals of DA neurons . However, the transition of DA neurons to a partially inactivated state of depolarization block has not been demonstrated in schizophrenic patients under treatment with neuroleptics.…”
Section: Introductionmentioning
confidence: 99%
“…In the striatum AADC mRNA is increased in response to chronic inhibition of DA receptors (Buckland et al, 1992) and its enzymatic activity is elevated in response to antagonists of DA D1 and D2 receptors (Zhu et al, 1992;Zhu et al, 1993;Hadjiconstantinou et al, 1993;Cho et al, 1997) while DA receptor agonists depress AADC activity (Hadjiconstantinou et al, 1993;Zhu et al, 1994;Cho 1997). In this context it is interesting to note that Reith et al (1994) found elevated AADC activity in patients with psychosis while more recently Lasko et al (2005) found evidence that an allele of the human DA D2 receptor gene (A1 allele) is associated with activity of striatal AADC in healthy subjects.…”
Section: Biosynthesis and Turnover Of The Trace Aminesmentioning
confidence: 99%